Clement of Alexandria's Paedagogus: a critical theory of global society and politics - Hrůšová, Veronika; Hoek, Annewies van den; Gyurkovics, Miklós (Vigiliae Christianae, 2025)
"This book is a collection of studies initially presented at the Third International Conference on Clement of Alexandria, which was focused on the Paedagogus. Although on the surface the Paedagogus seems to be more easily accessible than Clement's lengthier Stromateis or his fragmentary Excerpta ex Theodoto, the studies show that a profound theological undercurrent runs through the three books of the Paedagogus - the first focusing on the Logos, and the other two on ethics. Contributors: Emanuela Prinzivalli, Veronika Hrůšová, Miklós Gyurkovics, Edward Creedy, Marco Rizzi, Annewies van den Hoek, Vít Hušek, Léon-Ferdinand Karuhije, Lenka Karfíková, Ilaria L.E. Ramelli, Riemer Roukema, Jana Plátová, Johannes Aakjær Steenbuch, Dawn LaValle Norman, Carlo Perelli"--